Roles of conserved active site residues in the IscS cysteine desulfurase reaction - Pang, Yilin; Wang, Jing; Gao, Xueping; Jiang, Mengyao; Zhu, Lifei; Liang, Feng; Liang, Mengxiang; Wu, Xiaolin; Xu, Xianxian; Ren, Xiaojun; Xie, Ting; Wang, Wu; et al. (Frontiers in Microbiology, 2023)
Escherichia coli cysteine desulfurase (CD), IscS, modifies basal metabolism by transferring sulphur from L-cysteine to numerous cellular pathways, whereas NFS1, a human CD, is active only in the formation of the [Acp]2:[ISD11]2:[NFS1]2 complex. Despite the accumulation of red-coloured IscS in E. coli cells as a result of the deficiency of accessible iron, as revealed in our previous studies, the mechanism of the potential enzymatic reaction remains unclear. In this study, the N-terminus of IscS was fused with the C-terminus of NFS1, which was reported to be almost fully active as IscS and exhibits a pyridoxal 5’-phosphate (PLP) absorption peak at 395 nm. Moreover, SUMO-EH-IscS exhibited significant growth recovery and NADH-dehydrogenase I activity in the iscS mutant cells. Furthermore, through in vitro and in vivo experiments combined with high-performance liquid chromatography and ultra-performance liquid chromatography-tandem mass spectrometry, it was shown that the new absorption peaks of the IscS H104Q, IscS Q183E, IscS K206A, and IscS K206A&C328S variants at 340 nm and 350 nm may correspond to the enzyme reaction intermediates, Cys-ketimine and Cys-aldimine, respectively. However, after mutation of the conserved active-site residues, additional absorption peaks at 420 nm and 430 nm were associated with PLP migration in the active-site pocket. Additionally, the corresponding absorption peaks of Cys-quinonoid, Ala-ketimine, and Ala-aldimine intermediates in IscS were 510 nm, 325 nm, and 345 nm, respectively, as determined by site-directed mutagenesis and substrate/product-binding analyses during the CD reaction process. Notably, red IscS formed in vitro by incubating IscS variants (Q183E and K206A) with excess L-alanine and sulphide under aerobic conditions produced an absorption peak similar to the wild-type IscS, at 510 nm. Furthermore, mutations at Asp180 or Lys206 inhibited the reaction of IscS in vitro with L-cysteine (substrate) and L-alanine (product). These results suggest that the conserved active site residues (His104, Asp180, and Gln183) and their hydrogen bond with PLP in the N-terminus of IscS play a key role in determining whether the L-cysteine substrate can enter the active-site pocket and regulate the enzymatic reaction process. Therefore, our findings provide a framework for evaluating the roles of conserved active-site residues, motifs, and domains in CDs.